New Constraints on the Main Mineralization Event Inferred from the Latest Discoveries in the Bor Metallogenetic Zone (BMZ, East Serbia) - Banješević, Miodrag; Cvetković, Vladica; von Quadt, Albrecht; Ljubović Obradović, Darivojka; Vasić, Nebojša; Pačevski, Aleksandar; Peytcheva, Irena (Minerals (Basel), 2019)
This study aims at better constraining the link between magmatism and metallogeny in the south-easternmost sector of the Bor Metallogenetic Zone (BMZ), where the world-class copper and gold deposit of Čukaru Peki was recently discovered. The obtained U/Pb zircon ages confirm the earlier knowledge that the major Cu–Au porphyry and epithermal mineralization in the BMZ is genetically related to the first volcanic phase (‘Timok andesite’; 85–90 Ma). However, the data also suggest that during this phase, two subgroups of andesite porphyry were formed; they are named volcanic phase 1A (V1A) and volcanic phase 1B (V1B). The V1A andesite (89–90 Ma) is plagioclase-hornblende phyric, holocrystalline and ubiquitously hydrothermally altered and/or mineralized, whereas the V1B (85–86 Ma) is hornblende-plagioclase phyric, holo- to hypocrystalline, fresh, and non-mineralized. According to our simplified model, the contrasting productivity of the V1A and V1B is explained by fluctuations during AFC (assimilation-fractional crystallization) processes of water-rich parental magma, which have controlled the order of crystallization of hornblende and plagioclase in the V1A and V1B andesite.